2015
DOI: 10.1074/jbc.m115.691147
|View full text |Cite
|
Sign up to set email alerts
|

The Cysteine-rich Domain of the DHHC3 Palmitoyltransferase Is Palmitoylated and Contains Tightly Bound Zinc

Abstract: DHHC palmitoyltransferases catalyze the addition of the fatty acid palmitate to proteins on the cytoplasmic leaflet of cell membranes. There are 23 members of the highly diverse mammalian DHHC protein family, all of which contain a conserved catalytic domain called the cysteine-rich domain (CRD). DHHC proteins transfer palmitate via a two-step catalytic mechanism in which the enzyme first modifies itself with palmitate in a process termed autoacylation. The enzyme then transfers palmitate from itself onto subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…As shown in Fig. 7D, mutation of the PPFP sequence to APFA did not abolish Src-ZDHHC3 interaction, suggesting that other sites can be involved in enzyme-substrate interaction in the case of Srcmediated ZDHHC3 phosphorylation (23).…”
Section: Fgf2 Treatment Enhances Ncam Palmitoylation In Vivomentioning
confidence: 76%
“…As shown in Fig. 7D, mutation of the PPFP sequence to APFA did not abolish Src-ZDHHC3 interaction, suggesting that other sites can be involved in enzyme-substrate interaction in the case of Srcmediated ZDHHC3 phosphorylation (23).…”
Section: Fgf2 Treatment Enhances Ncam Palmitoylation In Vivomentioning
confidence: 76%
“…First, palmitate is attached to the cysteine in the DHHC motif[69]. This autoacylation reaction results in formation of an acyl-enzyme intermediate, which then transfers palmitate to a cysteine residue within the acceptor protein substrate.…”
Section: Protein Palmitoylationmentioning
confidence: 99%
“…This autoacylation reaction results in formation of an acyl-enzyme intermediate, which then transfers palmitate to a cysteine residue within the acceptor protein substrate. Structural integrity of DHHC enzymes is maintained by coordination of two zinc ions to conserved cysteines within the cysteine rich domain[69]. Although mutation of the DHHC cysteine residue typically generates an inactive enzyme mutant, there are examples of yeast DHHC proteins that can function at reduced efficiency with alanine or arginine in place of the DHHC cysteine[70].…”
Section: Protein Palmitoylationmentioning
confidence: 99%
“…Most importantly, PATs also have a highly conserved catalytic Asp-His-His-Cys Cysteine Rich Domain (DHHC-CRD) of ~50 amino acids (Roth et al, 2002). This domain was proposed as Cx2Cx9HCx2Cx4DHHCx5Cx4Nx3F (Mitchell et al, 2006), usually residing on the cytoplasmic face of membranes between transmembrane domains (TMD) 2 and 3 of PATs (Gottlieb et al, 2015). It was reported that mutation of cysteine in DHHC domain inhibits both acyl intermediate formation and acyl chain transfer activity of PATs (Mitchell et al, 2006; Gottlieb et al, 2015).…”
Section: Protein S-acyl Transferases (Pats)mentioning
confidence: 99%
“…This domain was proposed as Cx2Cx9HCx2Cx4DHHCx5Cx4Nx3F (Mitchell et al, 2006), usually residing on the cytoplasmic face of membranes between transmembrane domains (TMD) 2 and 3 of PATs (Gottlieb et al, 2015). It was reported that mutation of cysteine in DHHC domain inhibits both acyl intermediate formation and acyl chain transfer activity of PATs (Mitchell et al, 2006; Gottlieb et al, 2015). Indeed, when cysteine residue in the DHHC motif of AtPAT24, AtPAT10 and AtPAT14 of Arabidopsis was mutated to alanine or serine, all 3 AtPATs lost their PAT activities (Hemsley et al, 2005; Qi et al, 2013; Li et al, 2016).…”
Section: Protein S-acyl Transferases (Pats)mentioning
confidence: 99%